PENGENALAN INTERNET OF THINGS IOT BAGI SISWA YAYASAN CAHAYA ISLAM MUTIARA IMANI GUNA MEMANFAATKAN KEMAJUAN TEKNOLOGI MASA KINI - Vindua, Raditia; Nursakinah, Badriah; Nurhayati (Abdi Jurnal Publikasi, 2024)
Technological advances not only make human work easier, but can also reduce human involvement in an activity. In other words, the sophistication of existing technology can enable electronic devices to always be connected to the internet and will automatically be able to carry out commands according to the user's desired program, where air conditioners, computers, printers, lamps and other electronic equipment can be operated automatically. automatically functions according to previously input commands or by utilizing a database which is then processed with Artificial Intelligence logic so that it can generate commands automatically. Basically what you need to know is that a school is an institution for teaching and learning activities as well as a place for receiving and giving lessons. School is a place for students to study and is trusted by the community as a place to learn, train skills and even the process of maturing children by absorbing education from school in accordance with the function of the school itself, namely filling children's brains with various kinds of knowledge. Therefore, to increase the knowledge and understanding of students at the Cahaya Islam Mutiara Imani Foundation regarding current technological developments, training was created in the context of community service regarding Introduction to the Internet of Things (IoT). IoT technology is a trend in the digitalization era that can facilitate human activities by integrating several devices that will be connected to the internet network. In other words, IoT technology has helped many schools provide the best learning experience. Where learning institutions that have not yet embraced IoT technology are hastened to embrace and adapt to this IoT technology trend. Where the role of IoT in the world of education is to provide a comfortable learning experience. This also includes the infrastructure needed so that IoT can work optimally. The advantages of IoT technology that can be used in the education sector include that it can increase learning engagement, can provide space for personalized learning and provides extraordinary media and access for students with special needs. The aim of introducing and implementing the Internet of Things itself is apart from increasing insight into Internet of Things technology and the function of IoT itself, it is hoped that the material presented by the PKM team can increase knowledge for students at the Cahaya Islam Mutiara Imani Foundation. Community service activities can be organized well and run smoothly in accordance with the activity plans that have been prepared. This activity was very well received as evidenced by the participants' active participation in the entire event process and the question and answer session regarding the material provided.